2019
DOI: 10.1128/aac.01806-18
|View full text |Cite
|
Sign up to set email alerts
|

Pep5, a Fragment of Cyclin D2, Shows Antiparasitic Effects in Different Stages of the Trypanosoma cruzi Life Cycle and Blocks Parasite Infectivity

Abstract: Pep5 (WELVVLGKL) is a fragment of cyclin D2 that exhibits a 2-fold increase in the S phase of the HeLa cell cycle. When covalently bound to a cellpenetrating peptide (Pep5-cpp), the nonapeptide induces cell death in several tumor cells, including breast cancer and melanoma cells. Additionally, Pep5-cpp reduces the in vivo tumor volume of rat glioblastoma. Chagas disease, which is caused by the flagellated parasite Trypanosoma cruzi, is a neglected disease that occurs mainly in the Americas, where it is conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The infective form of T. cruzi , i.e., trypomastigotes, pre-treated with Pep5-cpp was unable to infect LLC-MK2 cells. These data suggest that Pep5 can be used as a novel alternative for the treatment of Chagas disease [78]. Altogether, these findings highlight the therapeutic potential of Pep5.…”
Section: Pharmacological and Biochemical Analyses Of Intracellularmentioning
confidence: 86%
“…The infective form of T. cruzi , i.e., trypomastigotes, pre-treated with Pep5-cpp was unable to infect LLC-MK2 cells. These data suggest that Pep5 can be used as a novel alternative for the treatment of Chagas disease [78]. Altogether, these findings highlight the therapeutic potential of Pep5.…”
Section: Pharmacological and Biochemical Analyses Of Intracellularmentioning
confidence: 86%
“…It was shown that it participates in protection from cell death [ 170 ]. Another example is the peptide Pep5 derived from cyclin D2, which influences cell death in different types of tumor cells [ 171 , 172 ].…”
Section: Biological Function Of Different Peptide Groupsmentioning
confidence: 99%